Ras Signaling: Divide and Conquer - Holderfield, Matthew (Nat Chem Biol, 2016)
The role of Ras dimerization in tumor biology is an emerging area of preclinical cancer research. Characterization of a Ras monobody indicates that dimer formation is required for Ras signaling revealing the dimer interface as a potential drug target.